The Influence of Person–Job Fit on Health Status and Depression Among Chinese Domestic Workers: Mediating Effect of the Employer–Employee Relationship - Chen, Lijuan; Jilili, Maitixirepu; Wang, Ruolin; Liu, Linping; Yang, Anuo (Frontiers in Psychology, 2022)
Domestic workers usually perform manual work in households. Unlike fixed work, their work tends to be individualized and atomized. Their person-job fit and relationship with employers might exert some influence on their health, both physical and psychological. This quantitative study explores the association between person–job fit, health status, and depression depressive symptoms among Chinese domestic workers by identifying the employer–employee relationship as a mediator. Data is collected from a survey of Chinese domestic workers conducted in four cities of Nanjing, Wuxi, Guangzhou, and Foshan (N = 1,003) in 2019. We test our theoretical model by conducting structural equation modeling. The results show that demand–ability fit is indirectly related to heath status and depressiondepressive symptoms via the employer–employee relationship. Need–supply fit is significantly associated with health status and depressive symptomsdepression both directly (70% for health status and 72% for depressive symptoms, separately) and indirectly, via the mediating effect of the employer–employee relationship (30% for health and 28% for depressive symptoms, separately). Our findings suggest that appropriate policy and vocational training should be implemented to improve the health status of Chinese domestic workers.